2018
DOI: 10.1248/yakushi.18-00094
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Time-to-onset and Onset-pattern of Interstitial Lung Disease after the Administration of Monoclonal Antibody Agents

Abstract: The aim of this study has been to investigate the time-to-onset and onset-pattern of drug-induced interstitial lung disease (DILD) after the administration of monoclonal antibodies through the use of the spontaneous adverse reaction reporting system of the Japanese Adverse Drug Event Report database. DILD datasets for adalimumab, bevacizumab, cetuximab, denosumab, golimumab, in‰iximab, nivolumab, panitumumab, pembrolizumab, tocilizumab, and trastuzumab were used to calculate the median time-to-onset of DILD, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 37 publications
0
9
1
Order By: Relevance
“…In this study, the median onset time was 49 days. 10 Likewise, Osawa et al 5 determined that the onset time varies between 2-313 days and did not find a specific onset time. Additionally, there were no significant correlations between the onset time of ILD and the radiological findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the median onset time was 49 days. 10 Likewise, Osawa et al 5 determined that the onset time varies between 2-313 days and did not find a specific onset time. Additionally, there were no significant correlations between the onset time of ILD and the radiological findings.…”
Section: Discussionmentioning
confidence: 99%
“…5 Generally, ILD's pathophysiological mechanism is defined as the induction of fibrosis due to direct toxicity, phospholipoid accumulation in alveolar immune cells, and immune-mediated lung toxicity. 10 Osawa et al 5 identified the risk factors of panitumumab induced ILD as history or complication of ILD, male sex, poor general condition, age of 65 or above. In this study, previous chemotherapy regimens and smoking history were not considered apparent risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the Weibull distribution is used to detect the signals for adverse events by utilizing time-to-events date. [14][15][16][17] Thus, we evaluated the time-to-onset of ganciclovir-induced adverse events using Weibull distribution parameters. The results of both scale parameter α and shape parameter β of total adverse events in JADER suggested that ganciclovir-induced adverse reactions including cytopenia, leukopenia and liver damage develop early in most cases (the early failure type) ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…However, on the other hand, a study on ILD related to the administration of monoclonal antibodies which includes denosumab has been recently reported [ 6 ] . The aim of this analysis was to investigate the time-to-onset and onset pattern of drug-induced ILD after the administration of monoclonal antibodies through the use of the spontaneous adverse reaction reporting system of the Japanese Adverse Drug Event Report (JADER) database.…”
Section: Discussionmentioning
confidence: 99%